Efek Magnetisasi Spontan dan Karakteristik Transport Listrik Film Tipis TiO2:Co yang ditumbuhkan dengan Metode MOCVD - Horasdia Saragih; Pepen Arifin; Mohamad Barmawi (Institut Teknologi Bandung, 2005)
TiO2:Co thin films were grown on Si(100) substrate by MOCVD method. The Co content in the film was varied in the range of 0.73% to 12.19%. The spontaneous magnetization effect and the electrical transport of films were measured by means of a Hall effect measurement. The Hall resistivity as a function of the magnetic field data show that the spontaneous magnetization effect occurs in films at the field lower than 1500 Oe. The Hall resistivity increases with the increase of Co concentration. The measurement of resistivity as function of temperature shows that the films have semiconductive properties. The minimum resistivity increases with increasing Co.